Teori dan Konsep Kompetensi Supervisor Pendidikan berbasis Prophetic Intelligence - Fatah Suparman; Meti Fatimah; Joko Subando (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this research is to understand the concept of Prophetic intelligence and its relation to Educational Supervisor Competence. The methods used are literature review and theoretical analysis. A qualitative approach is employed to obtain a deep understanding of the related theories and concepts. Through a comprehensive literature search, the researcher examined relevant theoretical sources such as books, articles, and research studies. The information gathered was then analyzed theoretically to establish a solid theoretical foundation and gain insights into the application of Prophetic intelligence in the context of Educational Supervisor Competence. This study concludes that the concepts of educational supervisor competence and prophetic intelligence have a positive impact on educational development. Educational supervisors who possess leadership skills, effective communication, decision-making abilities, conflict management skills, employee development capabilities, and managerial skills can ensure the effective implementation of educational programs and enhance the quality of teaching and learning. Meanwhile, individuals with high prophetic intelligence based on the concept of prophetic intelligence can incorporate religious values into their daily lives, maintain integrity, and refrain from engaging in misconduct. In the educational context, educational supervisors play a crucial role in ensuring that teachers understand and apply the concept of prophetic intelligence in the learning process, thereby creating an educational environment that is oriented towards religious values, integrity, and a commitment to truth and morality. The findings of this research indicate that the integration of educational supervisor competence and prophetic intelligence concepts can have a positive impact on effective and meaningful educational development.